Effect of Mycorrhizal Inoculation on Growth and Nutrients Uptake of Maize Grown on Crude Oil Contaminated Soil - Kingsley Uzoma; Michael E. Nkereuwem; Uzaifa K. Adamu; Adeniyi O. Adeleye; Abe Mololuwa (CV. Literasi Indonesia, 2021)
This study was carried out to evaluate the effect of mycorrhizal inoculation on the growth and nutrients uptake of maize planted in crude oil-contaminated soil. About 10 kg sterilized topsoil was contaminated with Bonny light crude oil (BLCO) at different concentrations: 0, 200, 300, and 500 ml/pot. Maize was sown at three seeds per pot and later thinned to two stands per pot after two weeks. Inoculation in treatments containing AM consisted of 20 g of Glomus clarum. Data on residual TPH content of the soil, plant height, number of leaves, fresh and dry weights, and nutrients uptake were collected at 4, 8, and 12 weeks after sowing (WAS). The 2 x 4 factorial experiment was laid in a completely randomized design and replicated 3 times. The results obtained indicated that AM inoculated maize had higher and significantly (p˂0.05) nitrogen, phosphorus, potassium, calcium, plant height, number of leaves, fresh and dry weights. Significantly (p˂0.05) lower residual TPH content was recorded with treatments inoculated with AM fungi compared to non-AM fungi inoculated treatments. AM colonization resulted in enhanced nutrients uptake thus, improving the physiological parameters of the test crop.